VARIATION OF NAVICULA MUTICOPSIS VAN HEURCK VAR. MUTICOPSIS F. MURRAYI (W. & G.S. WEST) KO-BAYASHI (PENNATAE DIATOM) FROM ANTARCTICA - Tsuyako KO-BAYASHI (National Institute of Polar Research, 1963)
Navicula muticopsis collected from Bybog Osane, the Antarctic continent, were mounted with pleurax for making permanent preparation, after being treated with acid. Then 389 individuals were selected at random and microphotographs were taken. Each microphotograph was enlarged 2,000 times in order to investigate the shells of this species. Among these materials, the most numerous were the species of which both ends of the shells were capitate and the center of the shell margins were convex (which is hitherto called Navicula gloviceps var. amphicephala). There were some which had linear shells and were convex at the center (which is hitherto called Navicula gloveiceps var. elongata or Navicula murrayi according to its protrusion), and some which had shells with rostal ends (which is hitherto called Navicula murrayi var. elegans). These varieties were connected by many intermediate links and therefore, they should be identified as wandering varieties of the same species, although these are devided into many species or varieties having many specific names. Some individuals, which had shells with rostal capitate ends, were found. These individuals could be classified as Navicula muticopsis but the number of individuals found is so few that the writer likes to identify it as a variety of Navicula muticopsis. The name is given as "Navicula muticopsis van Heurck var. muticopsis f. murrayi comb. nov.". The shapes of this variety are numerous and the shape and width of axial area are numerous, such as narrow linear, linear lanceolate, narrow lanceolate. The measurement of the shell of this variety: Length of shell : 14-58μ Width of shell : 7-13μ Number of striae in 10μ : 12-17